2006
DOI: 10.1007/bf03219106
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-drawing of gel films of ultra high molecular weight polyethylene/low molecular weight polymer blends containing BaTiO3 nanoparticles

Abstract: The ultra-drawing process of an ultra high molecular weight polyethylene (UHMWPE) gel film was examined by incorporating linear low-density polyethylene (LLDPE) and BaTiO 3 nanoparticles. The effects of LLDPE and the draw ratios on the morphological development and mechanical properties of the nanocomposite membrane systems were investigated. By incorporating BaTiO 3 nanoparticles in the UHMWPE/LLDPE blend systems, the ultra-drawing process provided a highly extended, fibril structure of UHMWPE chains to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The development of anisotropy is very apparent in the images. Un-drawn samples showed in Figure 2a show the lamellar structures [12]. The lamellar structure is transformed into oriented fibrous structure as is evident from the drawn samples 2b and 2c.…”
Section: Optical Transparency Of the Uhmwpe And Uhmwpe Nanocomposite mentioning
confidence: 74%
See 1 more Smart Citation
“…The development of anisotropy is very apparent in the images. Un-drawn samples showed in Figure 2a show the lamellar structures [12]. The lamellar structure is transformed into oriented fibrous structure as is evident from the drawn samples 2b and 2c.…”
Section: Optical Transparency Of the Uhmwpe And Uhmwpe Nanocomposite mentioning
confidence: 74%
“…Although UHMWPE possesses many excellent properties but its poor adhesion to fillers, lower thermal stability, high melt viscosity and creep are the main hurdles for its vast spread engineering applications. Many researchers have shown that nanofillers can be incorporated into UHMWPE matrix via in-situ polymerization [9,10], solution casting [11][12][13][14][15][16][17] and melt mixing [18][19][20] to improve thermal, mechanical, electrical, UHMWPE-filler adhesion, fluidity and reduce flammability of the pristine UHMWPE.…”
Section: Introductionmentioning
confidence: 99%